Soft pneumatic gripper integrated with multi‐configuration and variable‐stiffness functionality. Issue 1 (25th February 2021) - Yuan, Zean; Wu, Li; Xu, Xiangjian; Chen, Rui
Abstract: Soft grippers are compliant and self‐adaptive, and can be highly compatible with the surrounding environment in grasping tasks. Currently, most soft pneumatic grippers are developed with a single grasping configuration, which leads to poor universality for different objects. Additionally, the oscillation caused by actuator's elastic bodies will result in poor stability during grasping and transportation, which can be improved by stiffness enhancement. A four‐fingered soft pneumatic gripper is proposed by integrating multi‐configuration and variable‐stiffness functionality. The multi‐configuration was realised by using the motion characteristics of a tangent mechanism. Meanwhile, a damping method based on electrorheological fluids was applied on a pneumatic actuator to improve the grasping stability. Besides, a machine vision technique was adopted to automatically adjust the grasping posture during manipulation. As a result, the proposed multi‐configuration gripper can self‐adaptively grasp different shapes of objects, especially two classical types, a pen canister as the flat cylinder and a cuboid box as the long cylinder. In addition, the electrorheological variable‐stiffness method was manifested to be applicable for reducing pneumatic finger vibration. This research is expected to improve the versatility and grasping stability of soft pneumatic grippers.